Thoracic central venous occlusion in patients without history of central vein catheterization - K. Thanu (2019)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND | 2019. Background: Thoracic central vein occlusion (TCVO) was a common problem in hemodialysis dependent patients. The major cause of TCVO is due to hemodialysis catheter, but the data of TCVO in patients without any history of previous catheterization in Asia is very limited. Materials and Methods: The authors collected data from computed tomographic venography (CTV) between January 2010 and December 2012. Patients that had clinical TCVO performed CTV were included consecutively. Baseline clinical data, the history of hemodialysis catheter placement, and CTV findings were recorded and analyzed. Results: Seventy-six patients were enrolled in the present study. Patient with previous hemodialysis catheterization in central vein had statistically significant higher incidence of TCVO (6.93 times) than those without history of hemodialysis catheter placement (p<0.0001). Twenty-two TCVO were found in the vein, which had hemodialysis catheter placed previously. In this group, CTV reveal external compression by aortic branch or aortic dissection in six patients. Conclusion: History of central venous cannulation was strongly associated with TCVO. However, TCVO could be found in patients who did not have a history of central vein catheterization. The external compression by aortic branch and dissection was also a cause of TCVO.